Peningkatan Keterampilan Berpikir Komputasional Siswa SMA N 2 Medan Melalui Pendekatan STEM - Leni Fauziah; Lisbet Ariati Rumahorbo; Agustina Aritonang; Rosliana Siregar (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Improving the quality of education in Indonesia can be developed through the implementation of educational reform. One form of educational reform can be carried out by using a learning approach that can help teachers produce experts using the STEM (Science, Technology, Engineering, and Mathematics) approach. Initial findings reveal that only around 47.8% of SMA N 2 Medan students (class This research aims to see the effectiveness of the STEM approach in improving the critical thinking skills of SMA N 2 Medan students. The research method used is an experimental design with Non Equivalent Control Group Design. The research subjects were students of SMA N 2 Medan. The results showed that the sig (2-tailed) Equal variances value was assumed to be 0.000 < 0.05. Therefore, Ho is rejected and Ha is accepted, which means there is a significant difference in critical thinking abilities after students use the Equal variance method. The STEM-PBL approach, compared with the innovative K13 approach. The average critical thinking skills scores of the control class in the pre-test and post-test were 38 and 79.5. The coefficient remains at 0.676 and is significant at 0.000. This means the correlation is positive. Therefore, learning with a STEM approach has proven to be effective in improving the critical thinking skills of SMA N 2 Medan students.